A methodology for the design of robust rollover prevention controllers for automotive vehicles using differential braking. (5th October 2010) - Chiu, Jimmy; Solmaz, Selim; Corless, Martin; Shorten, Robert
In this paper we apply recent results from robust control to the problem of rollover prevention in automotive vehicles. Specifically, we exploit results which provide controllers to robustly guarantee that the peak values of the performance outputs of an uncertain system do not exceed certain values. As a measure of performance for rollover prevention, we use the Load Transfer Ratio (LTR) and design differential-braking-based rollover controllers to keep the value of this quantity below a certain level; we also obtain controllers which yield robustness to variations in vehicle speed. We present numerical simulations using a nonlinear multi-body vehicle simulation model to demonstrate the effectiveness of our controllers in preventing rollover.